Implementasi Metode Ummi dalam Pembelajaran Membaca Al-Qur’an pada Peserta Didik Berkebutuhan Khusus ADHD di SMP Ibnu Sina Bandung - Husniah, Lu'Lu'; Surahman, Cucu; Sumarna, Elan (Universitas Pendidikan Indonesia, 2024)
In the transformation towards inclusive education, Islam is present to address the issue of discrimination through learning and teaching the Qur'an that can be felt by all learners, both normal and special needs, with attention deficit hyperactivity disorder (ADHD). This research shows that the practice of learning to read the Qur'an using the Ummi Method is suitable for implementation in students with ADHD special needs. The purpose of this study is to find out how the planning, implementation, and evaluation of learning to read the Qur'an affect students with ADHD special needs in first-level inclusive schools. This study used a descriptive qualitative design where data were collected through interviews with inclusive school principals, curriculum heads, ummi teachers, ADHD special needs learners, and accompanying teachers. Observations and documentation studies also reinforced the data in this study. The findings provide evidence that the planning of learning to read the Qur'an using the ummi method for students with special needs in inclusive schools has gone well. In the implementation process, it was found that the use of the drill method with an individualized approach made it easier to learn to read the Qur'an for students with ADHD special needs in inclusive classes. In the evaluation results, several obstacles were found that made it difficult to achieve the maximization of the targets of students with ADHD special needs in the form of easily disrupted concentration among students with ADHD special needs, the unavailability of learning using audiovisuals that can be a reinforcer for students' concentration, and the lack of competent Ummi teaching staff.